Medical Management of Inflammatory Bowel Disease among Canadian Gastroenterologists - J Jones; R Panaccione; ML Russell; R Hilsden (Canadian Journal of Gastroenterology)
BACKGROUND: Little is known about physician perceptions of and practices in using infliximab – a biological agent that was approved in Canada for the treatment of Crohn’s disease in 2001, and for ulcerative colitis in 2006.